High-speed railway embankments stabilization by using a plant based biopolymer - Aksoy, Huseyin Suha; Gor, Mesut (Parlar Scientific Publications, 2017)
Astragalus is a biopolymer, obtained from a plant that grows mostly in Turkey, Iran, Turkmenistan, Iraq, China, Korea, Japan, Syria, Mongolia and North Africa etc. In this study, the availability of Astragalus as an additive in the rail road fills is researched with regards to durability and strength parameters. A bump grows up when there is differential settlement between a bridge abutment and an approach embankment. The allowable differential settlement should be nearly equal to zero at high speed train railway embankments. For determining the proportion of Astragalus needed for reaching the maximum strength parameters, ten different soil samples were prepared with Astragalus content ranging from 0% to 10% by weight. The optimum moisture content (wopt), maximum dry density and strength parameters are figured out for all mixtures. Nowadays, the high resilience modulus (MR) fills are commonly used in high speed rail roads. These fills have a high energy absorption capacity and strength. The MR value can be determined through CBR (California Bearing Ratio) tests. According to the experimental studies, adding 1 % of Astragalus to the sandy soils was deemed suitable in terms of strength parameters, economy and CBR values. © by PSP.
Keywords: Astragalus; Biopolymer; Railway embankment design; Resilience modulus; Strength parameters; Unconfined compression test